Linking Entrepreneurial Knowledge to Business Performance through Competence - Ce Gunawan; Galih Raspati (Indonesian Journal of Business and Entrepreneurship Research, 2026)
The food and beverage (F&B) MSME sector plays a strategic role in Indonesia’s economy, particularly in supporting employment creation, value-added production, and local economic development. Grounded in the Resource-Based View (RBV), this study examines how entrepreneurial knowledge as an intangible resource contributes to business performance through entrepreneurial competence as a capability mechanism. This study aims to analyze the effect of Entrepreneurial Knowledge on Business Performance through Entrepreneurial Competence among F&B MSMEs in West Java. A quantitative approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected through a structured questionnaire from 110 F&B MSMEs in West Java selected using purposive sampling. The results show that Entrepreneurial Knowledge has a positive and significant effect on Entrepreneurial Competence and Business Performance. Entrepreneurial Competence also has a positive and significant effect on Business Performance . Furthermore, Entrepreneurial Competence significantly mediates the relationship between Entrepreneurial Knowledge and Business Performance. The model explains 9.6% of the variance in Entrepreneurial Competence and 46.9% of the variance in Business Performance. The positive Q²predict values for Entrepreneurial Competence and Business Performance indicate that the model has predictive relevance. These findings confirm that entrepreneurial knowledge improves business performance not only directly but also indirectly by strengthening entrepreneurial competence. The study contributes to RBV-based entrepreneurship literature by demonstrating the knowledge–competence–performance mechanism in the specific context of F&B MSMEs in West Java. Practically, the findings suggest that MSME development programs should integrate entrepreneurial knowledge enhancement with competency-based training, digital literacy, innovation capability, and sector-specific business assistance.